Case study report: Llaollao / Muhammad Izzan Syahmi Muhammad Yushri … [et al.] - Muhammad Yushri, Muhammad Izzan Syahmi; Azizan, Azhad; Zaidi, Mursyid; Azizan, Muhammad Kameel; Ruslan, Muhammad Syafiq; Abdull Aziz, Muhammad Haffizi (2023)
Llaollao is a company that has been established in 2009 and have many branches in Malaysia. Their mission to make their yogurt a product that is widely accepted for its enormous health benefits, as well as its extraordinary taste, with their customers being the inventors of their own creations, thanks to our infinite combination of topping. Their vision to be present worldwide, consolidating a stable, successful and lasting business model. In this research. We have seen the problems, findings and results that need to be focus and highlighted. We were able to identify several numbers of problems that weaken and reduce the level marketing effectiveness of the product. The problems are lack of flavour option towards the customer, lack of advertisement and lack of promotion. Lllaollao have wide toppings but they do not have other flavour for their yoghurt. That is why some reviews said that the customers are bored with the basic flavour of Llaollao yoghurt. Other than that, Llaollao lack of advertisement were because they did not have great deal of advertisement for the older people. With the current situations older generation who are not quite familiar with the social media will face several problems. The fact of lack of promotion Lllaollao have, Llaollao does not have a lot of exciting promotion to offer to their customers. Because of this, they cannot reach their target market and goals. Llaollao should provide new several flavour for their customer to maintain the loyalty of them. With the new flavour, customers will not get bored because of eating same flavour over and over again. Lllaollao should focus on their promotion and marketing parts. The reason is to make their customers stay loyal and fully satisfied them. Lasty, with all the problems, these are the recommendation that we have come out with.